Home-Time as a Surrogate Marker for Functional Outcome After Aneurysmal Subarachnoid Hemorrhage. Issue 12 (December 2018) - Stienen, Martin Nikolaus; Smoll, Nicolas Roydon; Fung, Christian; Goldberg, Johannes; Bervini, David; Maduri, Rodolfo; Chiappini, Alessio; Robert, Thomas; May, Adrien; Bijlenga, Philippe; Zumofen, Daniel; Roethlisberger, Michel; et al.
Abstract : Background and Purpose—: Commonly used tools to determine functional outcome after aneurysmal subarachnoid hemorrhage (aSAH) have limitations. Time spent at the patient's home has previously been proposed as a robust outcome measure after ischemic stroke. Here, we set out to validate home-time as an outcome measure after aSAH. Methods—: We examined prospectively collected data from a nationwide multicenter registry of aSAH patients admitted to a tertiary neurosurgical department in Switzerland (Swiss SOS [Swiss Study on Aneurysmal Subarachnoid Hemorrhage]; 2009–2015). We calculated mean home-time (defined as days spent at home for the first 90 days after aSAH) and 95% CIs for each category of modified Rankin Scale at discharge and 1-year follow-up, using linear regression models to analyze home-time differences per modified Rankin Scale category. Results—: We had home-time data from 1076 of 1866 patients (57.7%), and multiple imputation was used to fill-in missing data from the remaining 790 patients. Increasing home-time was associated with improved modified Rankin Scale scores at time of hospital discharge ( P <0.0001) and at 1-year follow-up ( P <0.0001). Within each of the 8 participating hospitals, the relationship between home-time and modified Rankin Scale was maintained. Conclusions—: Home-time for the first 90 days after aSAH offers a robust and easily ascertainable outcome measure, discriminating particularly well across better recovery levels at time of hospital discharge and at 1-year follow-up. This measure complies with the modern trend of patient-centered healthcare and research, representing an outcome that is particularly relevant to the patient. Clinical Trial Registration—: URL: https://clinicaltrials.gov . Unique identifier: NCT03245866. Abstract : Supplemental Digital Content is available in the text.